We are Here - Charles, Tami; Collier, Bryan (New York, NY : Orchard Books, an imprint of Scholastic Inc., 2023)
"Lyrical, affirmational, and bursting with love ... a poignant story about Black and Brown heritage and community ... Tami Charles shares the beauty and excellence in the history of the Black community, assuring Black and brown children of the extraordinary legacy from which they come"--
Keywords: Black people -- History; Juvenile literature; African Americans -- Juvenile literature; African American children -- Juvenile literature; Self-esteem in children -- Juvenile literature; Black people -- History; Picture books; Stories in rhyme